Antihypertensive medications and sexual function in women: baseline data from the SBP intervention trial (SPRINT). Issue 6 (June 2016) - Thomas, Holly N.; Evans, Gregory W.; Berlowitz, Dan R.; Chertow, Glenn M.; Conroy, Molly B.; Foy, Capri G.; Glasser, Stephen P.; Lewis, Cora E.; Riley, William T.; Russell, Laurie; Williams, Olubunmi; Hess, Rachel
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: Hypertension is a risk factor for the development of cardiovascular and kidney disease, but treatment can substantially reduce risks. Many patients avoid antihypertensive medications because of fear of side-effects. Although associations between antihypertensives and sexual dysfunction in men have been documented, it remains unclear whether antihypertensives are associated with sexual dysfunction in women. We conducted a cross-sectional analysis of baseline data from women in the Systolic Blood Pressure Intervention Trial (SPRINT) to evaluate the relations among class of antihypertensive medication and the outcomes: sexual activity and sexual function. Methods: SPRINT enrolled individuals 50 and older with hypertension at high risk for cardiovascular disease. A subset of participants completed questionnaires regarding quality of life, including sexual function. Antihypertensive class was determined by medications taken at baseline. Results: Of 690 women in the quality of life subset of SPRINT, 183 (26.5%) were sexually active. There were no significant differences in sexual activity among women taking one or more antihypertensives and women not taking any. Women taking an angiotensin-converting enzyme inhibitor or angiotensin receptor blocker had higher odds of sexual activity [odds ratio 1.66 (1.12–4.27), P  = 0.011]. Among sexually active women, the prevalence of sexual dysfunction was high (52.5%). No class of medication was associated with sexual dysfunction in the multivariable model. Conclusion: Angiotensin-converting enzyme inhibitor or angiotensin receptor blocker use was associated with higher odds of sexual activity. Although prevalence of sexual dysfunction was high, no single class of antihypertensive medication was associated with sexual dysfunction.